Experimental and Statistical Investigations for Tensile Properties of Hemp Fibers - Peyman Sadeghi; Quang Cao; Ragab Abouzeid; Mohammad Shayan; Meensung Koo; Qinglin Wu (Fibers)
This study investigated the tensile behaviors of hemp fiber bundles and examined how properties including tensile strength and Young’s modulus vary with the bundle diameter. Hemp fibers were extracted, degummed, and separated into bundles of different diameters ranging from less than 50 μm to over 150 μm. Tensile tests were conducted on these fiber bundles using a rheometer-based tensile testing machine. The results showed that hemp fibers exhibited a tensile strength of 97.33 MPa and a Young’s modulus of 3.77 GPa at a 50% survival probability. However, the scale parameters for breaking stress and Young’s modulus were determined to be 620.57 MPa and 29.88 GPa, respectively. As the fiber bundle diameter increased, the tensile strength decreased significantly. This was attributed to the higher probability of defects and irregularities acting as weakness points in larger fiber bundles. In contrast, Young’s modulus (stiffness) increased with increasing bundle diameter, likely due to improved fiber–fiber interactions. To further understand the variability and reliability of the tensile properties, statistical models were developed. The Weibull distribution analysis was applied, revealing critical insights into the variability of diameter, stress at break, Young’s modulus, and strain at break. The Weibull parameters provided a comprehensive understanding of the fibers’ mechanical reliability. Additionally, the Griffith model was employed to predict the strength and Young’s modulus based on fiber diameters, supporting the observation that thinner fibers generally exhibited higher tensile strength due to fewer defects. Overall, this work highlights the importance of understanding structure–property relationships in natural fibers like hemp for optimizing their performance in composites.